Analysis of clustering in wireless sensor networks - Stephen C, Arul; Abishek.B, Ebenezer; V.Rajendran, Dr (International Journal of Engineering and Technology, 2018)
Location based routing using Global Position System used for establishing the nodes in wireless sensor networks making uses of clustering along with the location based routing is used for faster reliable and reduced Hops with minimum energy consumption and by using of minimum spanning tree algorithm to achieve a shortest path in a network. Clustering in wireless sensor network is used for improving network lifetime. We propose effective method called enhanced route optimization in clustering is performed using minimum spanning tree algorithm.Â Â